2019
DOI: 10.1016/j.heliyon.2019.e02396
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the degradation potential of Acid blue 113 by different oxidants using quantum chemical analysis

Abstract: In this work, quantum chemical analysis was used to predict the degradation potential of a recalcitrant dye, Acid blue 113, by hydrogen peroxide, ozone, hydroxyl radical and sulfate radical. Geometry optimization and frequency calculations were performed at ‘Hartree Fock’, ‘Becke, 3-parameter, Lee–Yang–Parr’ and ‘Modified Perdew-Wang exchange combined with PW91 correlation’ levels of study using 6-31G* and 6-31G** basis sets. The Fourier Transform-Raman spectra of Acid blue 113 were recorded and a complete ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Moreover, the values of HOMO and LUMO were found to be −5.413 and −2.863 eV, respectively, whereas the difference in the energy (HOMO-LUMO energy gap) was 2.55 eV. Similar values were recently computed and reported for Acid Blue 113 by Asghar et al [63]. Figure 6 shows the HOMO and LUMO of AB129 obtained at B3LYP/6-31G** and a map of the electron density of the AB129 molecule.…”
Section: Formation Of By-productssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the values of HOMO and LUMO were found to be −5.413 and −2.863 eV, respectively, whereas the difference in the energy (HOMO-LUMO energy gap) was 2.55 eV. Similar values were recently computed and reported for Acid Blue 113 by Asghar et al [63]. Figure 6 shows the HOMO and LUMO of AB129 obtained at B3LYP/6-31G** and a map of the electron density of the AB129 molecule.…”
Section: Formation Of By-productssupporting
confidence: 85%
“…The initial coordinates of the AB129 structure were obtained with the Avogadro program [78]. The structure of the AB129 was further optimized using the Orca program package [79], and the results were validated with Gaussian 16 software [63], both in the gaseous and liquid phase at the B3LYP/6-31G** level of study, as suggested in a recent work on the Acid blue 113 oxidation [63]. Time-dependent density functional theory TD-DFT was used to predict the excited state properties of AB129.…”
Section: Quantum Chemical Analysismentioning
confidence: 99%
“…MEP maps have been considered as a real descriptor for the charge distribution along the molecular surfaces of the noncovalent bond donors and acceptors. Whereby MEP maps, low and high electron densities are identified by the colored maps, where blue and red sites are prone to nucleophilic and electrophilic attacks, respectively. In the current study, MEP maps were generated under field-free conditions and the effect of EEF using 0.002 au electron density contour.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from the calculated data that RO16 dye is quite reactive and exhibit good nucleophilic character and is a good electron donor because its low hardness and higher HOMO energy values. In some recently published research papers noted that ⋅OH radical is a powerful electron acceptor [53] …”
Section: Resultsmentioning
confidence: 99%